(untitled) (Research, Society and Development, 2022)
The objective of the work is to carry out research with academics from the 9th and 10th period of Inapós, on the conduct and use of management techniques in the care of children. Pediatric dentistry is a specialty aimed at caring for children and adolescents, and thus often faces psychological challenges. Anxiety and fear are problems in the consultation, causing difficulty for quality treatment. Behavioral techniques have to be planned with particularities so that a positive attitude occurs, causing relaxation, trust and a good relationship between the child and the dentist, thus reducing anxiety and fear. The most faced difficulty is when the child does not allow the treatment to be carried out, crying, screaming, moving around. These behaviors happen due to fear, trauma, physiological conditions, and other factors and so management techniques cannot be dispensed with. As there are some management techniques, a questionnaire will be carried out with questions regarding which techniques the students have already used, as well as which and how they obtained better results during the treatment. It is concluded that dental students are trained in theory, so that in practice they can execute what has been learned, so through the result of this research it will be possible to identify the main management techniques used in the Inapós school clinic and observe that when correctly employed, are able to encourage the child to behave properly, so that the treatment can be understood and executed correctly and successfully.